Stable field emission performance of SiC-nanowire-based cathodes - Kim, Dong-Wan; Choi, Young-Jin; Choi, Kyoung Jin; Park, Jae-Gwan; Park, Jae-Hwan; Pimenov, Sergei M.; Frolov, Vadim D.; Abanshin, Nikolay P.; Gorfinkel, Boris I.; Rossukanyi, Nikolay M.; Rukovishnikov, Alexander I. (IOP PUBLISHING LTD, 2008)
In this paper we report the fabrication and testing of diode-type low-voltage field emission display (FED) devices with SiC-nanowire-based cathodes. The SiC-nanowire FEDs (flat vacuum lamps) were characterized by low emission threshold fields (similar to 2 V mu m(-1)), high current density and stable long-term performance. The analysis of field emission data evidenced that the Schottky effect would have a considerable influence on the field emission from nanowire-based samples, leading to the true values of the field enhancement factor being significantly lower than those derived from Fowler-Nordheim plots.
Keywords: ELECTRON-EMISSION; CARBON NANOTUBES; NANORODS; GROWTH; FILMS